CRM through partnership project activities management at Banglalink Priyojon Program – the loyalty based platform - Chowdhury, Nirzhar (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.